Accelerated evolution of Vkorc1 in desert rodent species reveals genetic preadaptation to anticoagulant rodenticides. Issue 6 (25th April 2022) - Chen, Yan; Wang, Dawei; Li, Ning; Wang, Deng; Liu, Xiao‐Hui; Song, Ying
Abstract: BACKGROUND: Some rodent species living in arid areas show elevated physiological tolerance to anti‐vitamin K rodenticides (AVKs), which seems to be due to some unknown selective pressures that rodents may experience in desert habitats. Genes involved in the ϒ‐carboxylation of blood coagulation, including vitamin K epoxide reductase complex, subunit 1 ( Vkorc1 ), ϒ‐glutamyl‐carboxylase ( Ggcx ) and NAD(P)H quinone one dehydrogenase ( Nqo1 ) are associated with anticoagulant resistance, or some levels of elevated tolerance, in rodents. To detect whether the DNA sequences of the three genes are also under natural selection in the desert rodent species, we analyzed the Vkorc1, Ggcx and Nqo1 genes of the desert rodents and compared them with other rodent species. RESULTS: We found an accelerated evolutionary rate in Vkorc1 of desert rodents, especially in Mus spretus, Nannospalax galili and Psammomys obesus . By contrast, signals of positive selection were absent for Ggcx and Nqo1 in all species. Mapping the amino acid variations on the VKORC1 protein three‐dimensional model suggested most interspecific amino acid variations occur on the outer surface of the VKORC1 pocket, whereas most intraspecific amino acid changes and known AVK resistance mutations occurred on the inner surface and endoplasmic reticulum luminal loop regions. Some desert‐species‐specific amino acid variations were found on the positions where known resistance mutations occurred, indicating these variations might be related to the elevated physical tolerance to AVKs in desert rodents. CONCLUSION: The evolution of Vkorc1 has been accelerated in some desert rodent species, indicating genetic preadaptation to anticoagulant rodenticides. Positive selection and relaxed selection have been detected in Psammomys obesus and Nannospalax galili, indicating the two rodent species might also show tolerance to AVKs, which needs further verification. © 2022 Society of Chemical Industry. Abstract : Natural selection on the Vkorc1 sequences promotes the evolution of elevated physiological tolerance to anticoagulants in desert rodents.